Geotechnical engineering of dams - Fell, Robin (A.A. Balkema, 2005)
Geotechnical Engineering of Dams provides a comprehensive text on the geotechnical and geological aspects of the investigations for and the design and construction of new dams. In addition, much attention is paid to the review and assessment of existing dams. The main emphasis of this work is on embankment dams, but much of the text, particularly those parts related to geology, can be used for concrete gravity and arch dams. All phases of investigation, design and construction of a dam are covered. Detailed descriptions are given from the initial site assessment and site investigation program.